Bacteriological quality assessment of buffalo meat collected from different districts of Bangladesh with particular emphasis on the molecular detection and antimicrobial resistance of the isolated Salmonella species - Hasan, Mahedi; Kabir, S M Lutful; Rahman, Md Tanvir; Sarker, Yousuf Ali (Asian-Australasian Journal of Food Safety and Security, 2018)
The research project was conducted to assess the bacteriological quality of buffalo meat samples collected from three upazilas namely Haluaghat, Sreepur and Madhupur of Bangladesh under the districts of Mymensingh, Gazipur and Tangail respectively with particular emphasis on the molecular detection and antimicrobial resistance of the isolate Salmonella species. Total viable count (TVC), total staphylococcal count (TStaC) and total salmonella count (TSC) of meat samples were determined and the mean values of TVC, TStaC and TSC for the Haluaghat, Sreepur and Madhupur were log 8.30, log 7.94, log 8.15; log6.21, log 6.40, log 5.43 and log 4.76, log 4.82, log 4.56 CFU/gm respectively which exceeded the ICMSF recommendations values. The variation of TVC and TSC in meats of different buffalo markets was significant at 5% level where the variation of TStaC was significant at 1% level. Nevertheless no significant variation was demonstrated between the interactions of the three upazilas. Among the samples, 46.67% (n=14) were found to be associated with Salmonella spp. The Salmonella spp. were identified by observing black centered colonies on XLD agar, positive to MR test and negative to VP and Indole test. All isolates of Salmonella spp. were positive to 16s rRNA gene based PCR (574bp). All isolates of Salmonella species were susceptible to ciprofloxacin, streptomycin and gentamicin. All isolates of Salmonella spp. (n=14; 100%) were resistant to amoxicillin and few isolates also resistant to erythromycin, tetracycline, azithromycin and cephradine. The findings of this study revealed the presence of multidrug resistant Salmonella spp. in buffalo meat of Mymensingh, Gazipur and Tangail districts of Bangladesh that posseses a serious threat to public health. Asian Australas. J. Food Saf. Secur. 2018, 2(1), 12-20